Determination of Effects and Binding Properties of N-Nitrosomorpholine and N-Nitrosopyrrolydine on Human Acrosin by Thin Layer Chromatography (Annals of Medical Research, 2021)
None
Keywords: Human acrosin, Thin layer chromatography, Nitrosopyrrolydine, Nitrosomorpholine, Enzyme kinetic, Amino acid.